Implementasi Penguatan Pendidikan Karakter Melalui Pembelajaran Jarak Jauh di Masa Pandemi Covid-19 - Ishak, Maulana; Munawwarah, Hidayati; Sari, Kartika (LP2M IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2021)
Strengthening character for students is the main task of the world of education starting from pre-school, secondary school, and higher education, because it is a mandate of the Law. Strengthening character must be carried out even in the conditions of the Covid-19 pandemic, where all educational processes must be carried out through distance learning as stated in the Circular Letter of the Minister of Education and Culture. This research aims to photograph and describe how the implementation of character strengthening through distance learning (PJJ) during the co-19 pandemic. This research is a field research with a qualitative descriptive approach. This research is located at Muhammadiyah University Prof. Dr. HAMKA with research informants are the AIKA Institute, lecturers, and students. In obtaining the data, the authors used observation, interview, and documentation techniques. And in analyzing the data obtained by the author using the Miles and Huberman model analysis, with analytical activities including data reduction, data display, and conclusion drawing/verification. The results of this study are (1) the implementation of character values ​​through Al-Islam and Kemuhammadiyahan learning. AIKA is a core curriculum that specifically teaches students deep Islamic values. All AIKA courses must be taken by every student. The output of this learning is the formation of human learners who are pious, have noble character, are progressive and excel in science and technology as the embodiment of tajdid da'wah amar makruf nahi munkar. (2) Optimization of campus cooperation with parents of students. the role of the campus and parents is carried out as an effort to control the process of internalizing character values ​​during learning, because the campus and parents are an inseparable part of the development of students. (3) Through special character improvement programs, such as Student Baitul Arqam (BAM) activities, student recitations, learning to read the Koran, and dhuafa family assistance programs which are carried out in groups by each student taking Muhammadiyah courses.